Stressful life events and non-suicidal self-injury among Chinese adolescents: A moderated mediation model of depression and resilience - Wei, Chang; Li, Zhiyong; Ma, Tao; Jiang, Xiaxia; Yu, Chengfu; Xu, Qian (Frontiers in Public Health, 2022)
Stressful life events are associated with an increased risk of non-suicidal self-injury (NSSI) in adolescence, but the mechanisms explaining this association are unclear. Based on the experiential avoidance model of NSSI, and the protective factor model of resilience, the current study tested depression as a mediator and resilience as a moderator of this association. Chinese adolescents (N = 643; Mage = 15.91; 52.10 % female), anonymously completed self-report measures in classrooms. Results showed that stressful life events was linked to adolescent NSSI in part because of adolescent depression, and resilience was a protective factor that buffered this effect. These findings can inspire practitioners to pay attention to the interaction of risk factors and protective factors when providing prevention and intervention for adolescent NSSI.